2017
DOI: 10.1167/17.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Working memory load modulates microsaccadic rate

Abstract: Microsaccades are tiny eye movements that individuals perform unconsciously during fixation. Despite that the nature and the functions of microsaccades are still lively debated, recent evidence has shown an association between these micro eye movements and higher order cognitive processes. Here, in two experiments, we specifically focused on working memory and addressed whether differential memory load could be reflected in a modulation of microsaccade dynamics. In Experiment 1, participants memorized a numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 61 publications
6
66
2
Order By: Relevance
“…Analysis of microsaccade differences between experiments shows that the microsaccade rate was overall lower in Experiment 1 compared to Experiment 2 ( Figure 6). Microsaccade rate has been shown to decrease with high cognitive load (Dalmaso et al, 2017;Xue et al, 2017) and task difficulty (Siegenthaler et al, 2014). This is in line with the overall lower performance in Experiment 1 compared to Experiment 2 but is in contrast to the overall larger pupil size (relative to baseline) and larger effect of speech clarity in Experiment 2 compared to Experiment 1.…”
Section: Microsaccades Are Not Influenced By Semantic Ambiguity and Ssupporting
confidence: 67%
“…Analysis of microsaccade differences between experiments shows that the microsaccade rate was overall lower in Experiment 1 compared to Experiment 2 ( Figure 6). Microsaccade rate has been shown to decrease with high cognitive load (Dalmaso et al, 2017;Xue et al, 2017) and task difficulty (Siegenthaler et al, 2014). This is in line with the overall lower performance in Experiment 1 compared to Experiment 2 but is in contrast to the overall larger pupil size (relative to baseline) and larger effect of speech clarity in Experiment 2 compared to Experiment 1.…”
Section: Microsaccades Are Not Influenced By Semantic Ambiguity and Ssupporting
confidence: 67%
“…Dalmaso et al [ 31 ] also reported that working memory load is reflected in microsaccade rate and magnitude. From two experiments, results showed that microsaccadic rate drops in the rebound phase of a high demand task (200-400 ms after onset), compared to an easier task.…”
Section: Related Work: Eye Trackingmentioning
confidence: 99%
“…Microsaccades are increasingly understood to reflect an active attentional sampling mechanism which is mediated by the SC (Hafed et al, 2015;Krauzlis et al, 2018Krauzlis et al, , 2018Rolfs, 2009;Rucci and Poletti, 2015;Wang and Munoz, 2015). Accumulating work suggests that their occurrence is not automatic but rather modulated by the general state of the participant and by the availability of computational capacity, such that microsaccade incidence is reduced under high load (Dalmaso et al, 2017;Gao et al, 2015;Widmann et al, 2014;Yablonski et al, 2017). MSI is an extreme case for such an effect of attentional capture on ocular dynamics, interpreted as reflecting an interruption of ongoing attentional sampling so as to prioritize the processing of a potentially important sensory event.…”
Section: Microsaccadic Inhibition (Msi) Is a Reliable Correlate Of Acmentioning
confidence: 99%